Social and Behavioral Determinants of Motorcycle Accident Risk Among University Students in Medan, Indonesia - Raspiyahni; Nurhayati; Arrazy, Syafran (The Indonesian Institute of Science and Technology Research, 2025)
In Indonesia, traffic accidents are a frequent occurrence and a serious problem, involving many fatalities and material losses. Motorcycles are the vehicles most often involved in traffic accidents and often result in fatalities and injuries, especially among students. The occurrence of motorcycle traffic accidents among students in Indonesia is a serious issue that ranks first among the causes of death in the productive age group. This study aims to analyze the influence of various factors on the potential for traffic accidents among college students, including knowledge, attitudes, infrastructure, environment, parental roles, and peer influence. A quantitative design with a cross-sectional approach was used, involving 212 student respondents selected through purposive sampling. Data were collected through questionnaires and analyzed using the chi-square test. The results of the study showed a significant influence of gender (p = 0.000, PR = 2.372), knowledge (p = 0.047, PR = 1.696), attitude (p = 0.039, PR = 1.527), infrastructure and environment (p = 0.032, PR = 0.649), and peer influence (p = 0.042, PR = 1.511) on the potential for traffic accidents among students. However, there was no significant influence of parental support (p = 0.543, PR = 0.746) on the potential for traffic accidents in students. The findings of this study indicate that when these factors are improved, the risk of accidents can be minimized. It can be concluded that safe driving behavior among motorcycle riders influences the incidence of accidents among university students. Therefore, increasing driving safety education and improving social and environmental infrastructure are important aspects of reducing the number of traffic accidents among university students.